The Correlation Between Impaired Thyroid Hormone Sensitivity and Diabetic Nephropathy in Euthyroid Patients with Type 2 Diabetes Mellitus - Ma D; Zhao P; Gao J; Guo X; Han M; Zan X; Chen C; Lv X; Liu J (Diabetes, Metabolic Syndrome and Obesity)
Dengrong Ma,1 Pingping Zhao,1 Jie Gao,1 Xinyuan Guo,1 Mei Han,1 Xiaohui Zan,1 Chongyang Chen,1 Xiaoyu Lv,1 Jingfang Liu1,2 1The First Clinical Medical College, Lanzhou University, Lanzhou, Gansu Province, People’s Republic of China; 2Department of Endocrinology, the First Hospital of Lanzhou University, Lanzhou, Gansu Province, People’s Republic of ChinaCorrespondence: Jingfang Liu, Department of Endocrinology, The First Hospital of Lanzhou University, No. 11 Donggang West Road, Chengguan District, Lanzhou City, Gansu Province, People’s Republic of China, Tel +86-931-8356242, Email ljf824168@126.comPurpose: To investigate the association between impaired thyroid hormone sensitivity and diabetic nephropathy (DN) in euthyroid patients with type 2 diabetes mellitus (T2DM).Methods: 1305 euthyroid patients with T2DM who were hospitalized in the Endocrinology Department of the First Hospital of Lanzhou University between July 2021 and August 2023 were selected. Several indices, such as the parameters thyroid feedback quantile index (PTFQI), thyroid feedback quantile index (TFQI), thyroid stimulating hormone index (TSHI), serum-free triiodothyronine to free thyroxine (FT3/FT4) ratio, and thyrotropin thyroxine resistance index (TT4RI) to evaluate thyroid hormone sensitivity were used. The patients were subdivided into four groups (Q1 to Q4) based on the quartile levels of the five indices. The correlation between thyroid hormone sensitivity and DN was analyzed by binary logistic regression and restricted cubic spline (RCS) analysis.Results: The levels of PTFQI, TFQI, and TSHI in the DN group were higher than those in the Non-DN group [0.04(− 0.21, 0.31) vs − 0.003(− 0.27, 0.25), 0.05(− 0.20, 0.30) vs 0.006(− 0.26, 0.25), 2.54± 0.52 vs 2.47± 0.51, all P< 0.05], while the FT3/FT4 levels were decreased in the DN group (0.40± 0.07 vs 0.42± 0.07, P< 0.05). Multivariate logistic regression analysis showed that the increase in PTFQI and TFQI levels was positively correlated with DN [OR=1.518, 95% CI(1.074, 2.145) and OR=1.546, 95% CI(1.084, 2.204)]. RCS showed a linear dose-response relationship between PTFQI, TFQI, TSHI, FT3/FT4, TT4RI, and the tendency of DN (all Pnon-linear> 0.05). As the levels of PTFQI, TFQI, and TSHI increased, and the FT3/FT4 levels decreased, the prevalence of DN and the urinary albumin-to-creatinine (UACR) level showed an upward trend (all Ptrend test< 0.05), while the estimated glomerular filtration rate (eGFR) level showed a downward trend (all Ptrend test< 0.05).Conclusion: Among euthyroid patients with T2DM, impaired thyroid hormone sensitivity is associated with DN, as well as elevated UACR levels and decreased eGFR levels.Keywords: type 2 diabetes mellitus, thyroid hormone sensitivity, diabetic nephropathy